Vulnerability human rights, and comprehensive health care needs of young people living with HIV/AIDS - De Carvalho Mesquita Ayres, José Ricardo; Paiva, Vera; França Jr., Ivan; Gravato, Neide; Lacerda, Regina; Della Negra, Marinella; De Sousa Marques, Heloisa Helena; Galano, Eliana; Lecussan, Pilar; Segurado, Aluísio Cotrim; Silva, Mariliza Henrique (American Public Health Association, 2006)
We sought to identify and understand the health care needs of young people living with HIV/AIDS, particularly in terms of their psychosocial well-being. We conducted a qualitative analysis of HIV-positive young people and their caregivers, focusing on the implications of an HIV diagnosis for health care needs. Stigma was a recurrent issue that arose in the interviews conducted with the respondents, and it was evident that youths had been denied many rights related to health. We concluded that young people living with HIV need comprehensive care based on a human rights approach. In this regard, we offer some practical recommendations for health programs.